FRAUD PENTAGON AND POTENTIAL BANKRUPTCY AT PROPERTY & REAL ESTATE COMPANY - Justin Axel Irawan; Weli Weli (AJAR, 2022)
The purpose of this study is to analyze the effect of indicators on pentagon fraud on potential bankruptcy in property & real estate companies for the 2018 - 2020 reporting year. Pentagon fraud consists of indicators of pressure, rationalization, capability, arrogance, and opportunity while potential bankruptcy uses the Zmijewski model. Data was collected using content analysis methods from financial reports and annual reports obtained from the official website of the Indonesia Stock Exchange (IDX) and the company's official website. The method of data analysis was carried out using regression analysis with the help of SPSS software. The results of the analysis of 129 company report data show that only one indicator of the fraud pentagon has an effect on the potential for bankruptcy, namely pressure. There is no empirical support for other indicators, namely Rationalization, Capability, Arrogance and Opportunity for potential bankruptcy. This study provides a theoretical contribution to the study of the fraud pentagon and the potential for bankruptcy. A better understanding of indicators of fraud enables companies to prevent potential bankruptcy.